Vocabulary learning beliefs, strategies of form six students of SMK Sungai Tapang, Samarahan / Frankie Subon - Subon, Frankie (2011)
Vocabulary acquisition is one of the important determinants that enables students to be proficient L2 users. Students’ vocabulary size is built up through a variety of learning experiences. VL strategies are classified into ‘incidental’ and ‘intentional’ learning strategies that are present in taxonomies of VL learning strategies by Oxford (1990), Schmitt (1997), Sokmen (1997), etc. Notably, researchers have differing views on which strategy is the key to vocabulary acquisition. In recent years, researchers have begun to take into account all the strategies and recognize their influence on vocabulary learning (Gu & Johnson, 1996). In this study, a taxonomy of VL strategies by Gu & Johnson (1996) and Fan (2003) cited in Ming (2007) was used to identify the pattern of VL strategies of Form Six students. The results revealed that the samples had a medium frequency of strategy use with an overall mean of A/=3.21 (SD=.45). They had the highest frequency of use for guessing “I guess the meaning of words I don’t know” (M=3.80; SD=.94) and the least “I carry a pocket dictionary to look up the words I don't know” (M=2.22; SD= 1.17). Guessing strategy was the most frequently used strategy, followed by perception and encoding strategies. In contrast with previous research by Gu & Johnson (1996) and Ming (2007), management strategy turned out to be the least frequently used strategy. There were significant differences in strategy use by field of study and gender and a moderate positive correlation between attitude towards VL and strategy use, but there was no significant difference in strategy use in terms of self-rated English proficiency and no correlation between perception of problems in VL and strategy use. Thus, the implication is Form Six students should read extensively and practise meaning-focused reading to learn new vocabulary incidentally from context. They should also be made aware of effective strategies to use. Besides, direct instruction or intentional study such as the use of dictionary, activation and management strategies are still beneficial to enhance vocabulary acquisition and should not be neglected.